Citizen Radio Science: An Analysis of Amateur Radio Transmissions With e‐POP RRI. Issue 8 (6th August 2018) - Perry, G. W.; Frissell, N. A.; Miller, E. S.; Moses, M.; Shovkoplyas, A.; Howarth, A. D.; Yau, A. W.
Abstract: We report the results of a radio science experiment involving citizen scientists conducted on 28 June 2015, in which the Radio Receiver Instrument (RRI) on the Enhanced Polar Outflow Probe (e‐POP) tuned in to the 40‐ and 80‐m ham radio bands during the 2015 American Radio Relay League Field Day. We have aurally decoded the Morse coded call signs of 14 hams (amateur operators) from RRI's data to help ascertain their locations during the experiment. Through careful analysis of the hams' transmissions, and with the aid of ray tracing tools, we have identified two notable magnetoionic effects in the received signals: plasma cutoff and single‐mode fading. The signature of the former effect appeared approximately 30 s into the experiment, with the sudden cessation of signals received by RRI despite measurements from a network of ground‐based receivers showing that the hams' transmissions were unabated throughout the experiment. The latter effect, single‐mode fading, was detected as a double‐peak modulation on the individual dots and dashes of one of the ham's Morse coded transmissions. We show that the modulation in the ham's signal agrees with expected fading rate for single‐mode fading. The results of this experiment demonstrate that ham radio transmissions are a valuable tool for studying radio wave propagation and remotely sensing the ionosphere. The analysis and results provide a basis for future collaborations in radio science between traditional researchers in the academia and industry, and citizen scientists in which novel and compelling experiments can be performed. Plain Language Summary: We report the results of an experiment in which we used a satellite‐based radio receiver to eavesdrop on ham radio communications as the satellite passed over the United States. We identified 14 ham radio users by their call signs and used this information to determine their location during the experiment. We were able to identify unique signatures in the hams' signals that are directly related to the nature of the how the hams' radio waves traveled through the Earth's ionosphere up to the satellite. Furthermore, we used our knowledge of the position of the spacecraft and the location of the hams and their broadcast frequencies to deduce the structure of the Earth's ionosphere over the United States during the experiment. This experiment and its results show that ham radio transmissions and hams (amateur radio operators) can be valuable assets in determining the structure of the ionosphere over large geographic regions. Key Points: Amateur radio transmissions are used to detect plasma cutoff and single‐mode fading Fundamental ionospheric characteristics and magnetoionic phenomena can be studied with amateur radio transmissions New and compelling radio science experiments are possible with the participation of citizen radio scientists